Analisis Usability dalam User Experience pada Sistem KRS Online UMM menggunakan USE Questionnaire - Wahyu Andhyka Kusuma; Vebrian Noviasari; Gita Indah Marthasari (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2016)
KRS-Online system is a web-based information system to assist the process of preparing the KRS of every student in University of Muhammadiyah Malang. In this research, the level of usability of the system will be measured and the relationship between the independent variables (usefulness,ease of use, and ease of learning) and dependent variable (satisfaction), either simultaneously or partially, will be analyzed. Usability measurement adopted in this study is USE questionnaire that contains usefulness, ease of use, ease of learning, and satisfaction variables. This research involves 100 respondents from the KRS-Online system users. The result shows that measuring usability produces feasibility of 73.312%, which means usability of KRS-Online system is